Characteristics of Goat Milk Kefir with Addition of Red Yeast Rice Extract During Storage - Dilla Melani; Nurliyani Nurliyani; Indratiningsih Indratiningsih (Buletin Peternakan, 2021)
Kefir is one of milk products, produced by the addition of bacteria and yeast-containing kefir starter. This study aimed to evaluate the microbial characteristic, antibacterial activity, chemical and physical characteristics, antioxidant activity, and organoleptic characteristic of goat milk kefir which treated with angkak (red yeast rice) extract supplementation during storage. The study was initiated with milling to produce angkak flour, which then was diluted on sterilized distilled water on 1:2 ratio. Kefir were obtained by fermenting goat milk using 3% kefir grain for 18 hours at room temperature. Different treatments on the study were angkak extract supplementations on level of 0; 2; 4; and 6% for three different storage periods, i.e., 0, 7, and 14 days. The parameter of microbial characteristics observed on this study were total of lactic acid bacteria, TPC, total yeast, and antibacterial activity. Chemical tests performed on this study included the value of acidity, pH value, alcohol content, and water content. Meanwhile, the physical evaluations included viscosity, color test (brightness value, red value, and yellow value), and followed with antioxidant activity test on DPPH method and organoleptic test. Data from chemical, microbial, and physical evaluation were analyzed on one way ANOVA for these following parameters: total count of lactic acid bacteria, TPC, antibacterial activity, value of acidity, pH value, alcohol content, water content, viscosity, brightness value, red value, yellow value, antioxidant activity, and sensory values (alcoholic taste and acceptability). The analysis were further continued on two way ANOVA for total count of lactic acid bacteria, TPC, antibacterial activity on E. coli and S. aureus, alcohol content, viscosity, brightness value, red value, yellow value, and antioxidant activity. Meanwhile, the organoleptic characteristics were analyzed on non-parametric Kruskal Wallis, followed by Duncan’s multiple range test (DMRT).  Data were analyzed on computer program of Software Statistical Product and Service Solution (SPSS) version 18 for windows. The study revealed that angkak extract supplementation on goat milk kefir during 0, 7, and 14 days of storage had significant effects (P<0.05) on total count of lactic acid bacteria, TPC count, antibacterial activity, value of acidity, pH value, alcohol content, and sensory qualities (alcoholic taste and acceptability). There was an interaction between angkak extract supplementation and storage period on total count of lactic acid bacteria, TPC, antibacterial activity on E. coli and S. aureus, alcohol content, viscosity, brightness value, red value, yellow value, and antioxidant activity. As summary, supplementation of angkak extract at 6% level and 14 days storage periods increase the microbiological quality, viscosity, alcohol content, antioxidant activity, as well as its alcoholic taste-associated acceptability, and inhibit the growth of pathogens (E. coli and S. aureus).